MENGEMBANGKAN KREATIVITAS DAN KEMAMPUAN MENGGAMBAR PADA ANAK DOWN SYNDROME MELALUI TEKNIK MELENGKAPI GAMBAR - Andi Purnawan Putra; Bagus, Bagus Mahardika (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2024)
The ability to draw is the initial stage for children to express themselves and their emotions through various media. For children, drawing is the most enjoyable thing, but unfortunately children with special needs find this activity difficult to do, even just imitating the shape of objects, it is very difficult to imitate. This research aims to increase motivation and drawing skills in children with special needs through drawing completion techniques. Data collection techniques use observation, interviews and documentation. Data analysis uses data reduction, data presentation, and verification/drawing conclusions. Test the validity of the data using source triangulation and technical triangulation. The results of the research show that the technique of completing drawings can increase the motivation and drawing ability of children with Down syndrome, such as having high interest, honing skills and perseverance, developing the child's personality, and can be a means of therapeutic modality for children's mental health